Informatization of educational process in high school pedagogical direction - ЕROPOVA Еlena; MEDVEDEV, Yriy (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
Informatization is an important component of the system of higher education, which includes not only traditional methods and forms of training, but also the use of multimedia, telecommunications, remote sensing means of training. The use of it in teaching gives the possibility to the students carry out course and diploma projects with the use of the programs: Word text editor, Excel spreadsheets, drawings are done in AutoCAD or ArchiCAD, graphics, Power Point, Corel Draw and Photoshop. Thanks to the introduction of information technologies into the process of teaching students with an interest carry out the work, as it allows you to show the individual abilities and increases the cognitive interest in the subjects. Information technology is convenient to use when conducting ratings of the tests (with multiple choice answers, with alternative answers, with freely конструируемыми answers), the independent work of the students. Regular use of computer programs facilitates the acquisition of in-depth and profound knowledge, development of creative thinking and abilities, the formation of the students ’ motivation readiness to use the acquired knowledge, abilities and skills for the future profession of a teacher. Future specialists of the educational sphere should own it, to solve their professional tasks, successfully work with the children. Substantial assistance in this may have a modern information and computer technologies, without which the teachers of today are simply not do. Ability to use in their work modern it becomes one of the main components of professional training of teachers.